Amoras e jabuticabas: raízes e frutos de uma Pedagogia Profunda para todos - Hamer, Bruna Laselva [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
The present study was outline from the need to reconsider the purposes of education and the meaning of the schooling process. Current debates about education indicate great difficulty of educational systems to provide a quality educaiton, respecting the diversity and individuality in the school community. The reason, the scientific and technical knowledge, and specialty are highly valued in our culture, which is reflected in education. Thus, are offered to the child intellectual stimuli very early, while their body, their emotions, their intuition are silenced. Jungian Psychology, by considering, in addition to the personal unconscious of the human being, the existence of a collective unconscious, allows expanding the vision of man a rational only. The observation of the child from this perspective, justifies attention to their body, their dreams, their emotions, their intellect, their spirituality and how many other dimensions are presented. Education must then attend all their needs, aiming at a comprehensive education. With this goal was born Profound Pedagogy, which considers the child with its multiple dimensions. Its theoretical axis is based on Profound Psychology, still integrating the principles and practices of Sacred Circle Dances and Subtle Touches. The Profound Pedagogy does not propose a teaching methodology, but an enhancement of the educator, his personality, his vision of the human being and his knowledge of the child. Besides dancing and body works cited above, it includes working with matter, through artisan techniques and handwork, as well as jokes, games and toys confection. In this way, this study aimed to analyze the application of Profound Pedagogy's assumptions in a early childhood teacher's practice and evaluate whether the practice developed promotes service to diversity. It is featured as a case study, based on qualitative clinical methodology used in the methods of Life History, Narratives and Content Analysis...

A presente investigação se delineou a necessidade de reconsideração dos propósitos da educação e do sentido do processo de escolarização. Os debates atuais sobre a educação apontam grande dificuldade dos sistemas educativos em proporcionar um ensino de qualidade, respeitando a heterogeneidade e a individualidade na comunidade escolar. A razão, o conhecimento científico e técnico, e a especialidade, são fortemente valorizadas em nossa cultura, o que se reflete na área da educação. Assim, são oferecidos à criança estímulos intelectuais desde muito cedo, enquanto seu corpo, suas emoções, sua intuição vão sendo silenciadas. A Psicologia Junguiana, ao considerar, além do inconsciente pessoal do ser humano, a existência de um inconsciente coletivo, permite ir muito além da visão do homem como ser apenas racional. A observação da criança sob essa ótica, justifica a atenção ao seu corpo, seus sonhos, suas emoções, seu intelecto, sua espiritualidade e quantas outras dimensões se apresentem. A educação deve então atender todas as suas necessidades, visando uma formação integral. Com esse objetivo nasceu a Pedagogia Profunda, a qual considera a criança com suas múltiplas dimensões. Seu eixo teórico se baseia na Psicologia Profunda, integrando ainda princípios e práticas das Danças Circulares Sagradas e dos Toques Sutis. A Pedagogia Profunda não propõe uma metodologia de ensino, mas um aprimoramento do educador, de sua personalidade, de sua visão de ser humano e do seu conhecimento da criança. Além da dança e dos trabalhos corporais citados acima, ela inclui o trabalho com a matéria, por meio de técnicas artesanais e trabalhos manuais, assim como brincadeiras, jogos e confeção de brinquedos. Dessa forma, este estudo teve como objetivo analisar a aplicação dos pressupostos da Pedagogia Profunda na prática de uma docente de Educação Infantil e avaliar se a prática desenvolvida favorece o...
Blackberries and jabuticaba fruits: Roots and fruits of a Profound Education for everyone
Keywords: Jung, C. G. Carl Gustav 1875-1961; Educação; Psicologia; Dança; Education